Developing an Undergraduate Learning Approach to Enhance Ijtihad in Graphic Design Education in Yemen - Sabra, Nabil (Auckland University of Technology, 2024)
Bakry et al. (2019) note that critical thinking is an essential skill not only for educational achievement but also for enhancing one’s quality of life. Because to date, Yemeni graphic design education has not formally engaged with critical thinking, this study has drawn on adult learning theories, Islamic pedagogies, and the reflections of six teacher practitioners to shape a learning approach that might assist Yemeni graphic design educators to exercise the potentials of ijtihad in their classrooms. The study employed an Appreciative Inquiry that involved the collaboration of practitioners teaching across eleven universities and colleges in Yemen. The research is significant because it considers the potentials of a culturally specific mode of critical thinking and ways that it might be developed inside a Yemeni design education system, while advancing ways in which Appreciative Inquiry might operate in a non-Western context.